Resilient storage networking designing flexible scalable data infrastructures - Schulz, Greg. (Amsterdam ; Boston : Elsevier Digital Press, 2004)
A resilient storage network is an environment where data is always available for the needs of the business. This book explains the components, as well as how to design and implement a resilient storage network for workgroup, departmental, and enterprise environments. Storage networks are an enabling capability combining technology and best practices to provide the foundation to support information technology systems and applications. Storage networks can be of various sizes, shapes, and technologies. This book shows you how to implement a resilient storage network infrastructure using different technologies including ATM, DWDM, FCIP, Fibre Channel, FICON, iFCP, InfiniBand, IP, iSCSI, Life Cycle Management, NAS, Object Based Storage, RAID, RDMA, Remote Mirroring, Replication, SAN, SCSI, SMI-S, SONET/SDH, Storage Services, Tape, Virtualization, and Volume Managers. *Important information is clarified and put into context to separate myths and realities *Covers storage networking technologies (hardware, software, networks) and practices *Numerous tips and recommendations allow the reader to quickly understand best practices *Checklists, templates and examples show potential solutions.
Part I: Why Storage and Storage Networks? Importance of Information; Data Storage Fundamentals; Part II: Resilient Storage Networks: Networking Your Storage; Storage Network Design; Performance and Capacity Planning; Storage Management; SMIS; Storage and Storage Networking Virtualization; Part III: Networking with Your Storage: Storage and I/O Networks; Storage Networking Devices; Resilient Infrastructures; Securing Information; Part IV: Putting It All Together: Small SANs; Consolidation Examples; Metro and Wide Area; High Performance; Heterogeneous SANs; Wrap-up; Appendices: Storage Networking Information; RAID and Storage Information; Fiber Optic and Cabling Information; Glossary.
Includes index.
Keywords: Storage area networks (computer networks); Information storage and retrieval systems; Electronic books